KEDUDUKAN ORGANISASI KEMASYARAKATAN ASING DI INDONESIA DI TINJAU DARI PERATURAN PEMERINTAH NOMOR 59 TAHUN 2016 - Elwidarifa Marwenny; Engrina Fauzi; Jelisye Putri Cenery (JCH (Jurnal Cendekia Hukum), 2018)
One of the form of applying the value of democratic in Indonesia is accommodate by the regulation of community organization which is concretely regulated in the provisions of article 28 E Paragraph 3 of the 1945 constitution also in the provisions of law number 39 of 1999 on Human Rights. The existence of community organizations does have a great constribution in the implementation of the state, but on the other hand the existence of people raises the pro and contra. The enecment of government regulation number 59 on community organization established by foreign citizens makes the community more worried if the exixtance of community organizations affect the sovereignty of NKRI because they have different ideology with Indonesia. Based on this, it should be discussed about the organizations in Indonesia. The position of foreign social organizatios in Indonesia is reviwed from the government regulation number 59 of 2016 on community organizations established by foreign citizens and the influence of basic organizations for the sovereignty of NKRI. To answer that question, qualitative method is used  as a means to answer the problem by conducting of normative juridical approach which is done by reviewing the law and the literature. Based on this study, it is concluded that the existence of foreign social organizatios in Indonesia in line with  democracy and human right but also politically can treaten NKRI.